2011
DOI: 10.1603/me10226
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Phlebotomine Sand Flies on United State Military Operations at Tallil Air Base, Iraq: 6. Evaluation of Insecticides for the Control of Sand Flies

Abstract: We conducted a series of field experiments in 2003 and 2004 to evaluate the efficacy of a variety of insecticides and insecticide application technologies for the control of phlebotomine sand flies at Tallil Airbase, Iraq. During the experiments, 53,263 sand flies were collected. The experiments evaluated the following: (1) routine sand fly control operations using a variety of residual and area-wide insecticides; (2) a combination of five different insecticide application methods in and around tents; (3) resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…Additionally, zoonotic cutaneous leishmaniasis can seriously affect the operational readiness of United States military personnel deployed in Iraq and Afghanistan [41]. Attempts by the U.S. military to control sand flies through the use of chemical pesticides were not highly successful, possibly due to extreme environmental conditions [14,15], and pesticide bioassays did not reveal evidence of insecticide resistance. Chemical pesticides have been used in several ways for insect control, including area-wide applications for malaria control in the same areas inhabited by P. papatasi .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, zoonotic cutaneous leishmaniasis can seriously affect the operational readiness of United States military personnel deployed in Iraq and Afghanistan [41]. Attempts by the U.S. military to control sand flies through the use of chemical pesticides were not highly successful, possibly due to extreme environmental conditions [14,15], and pesticide bioassays did not reveal evidence of insecticide resistance. Chemical pesticides have been used in several ways for insect control, including area-wide applications for malaria control in the same areas inhabited by P. papatasi .…”
Section: Discussionmentioning
confidence: 99%
“…Use of synthetic sand fly pheromone as an attractant was reported to improve effectiveness of pesticide application for control of the new world sand fly Lutzomyia longipalpis in chicken sheds [13]. Attempts to control Phlebotomus papatasi by various types of insecticide application has had questionable effectiveness, particularly in the harsh environments reported during combat operations by the U.S. military in Iraq [14,15], although there was no evidence of significant insecticide resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our surveillance program, we do not know whether our ULV missions had any impact on sand fly populations. Coleman et al (2011) found that various insecticide applications, including ULV, did not have a significant effect against sand flies in southern Iraq.…”
mentioning
confidence: 95%
“…By contrast, in an earlier CanL modelling article, Dye [9] concluded that insecticide use was more effective than vaccination. However, Dye [9] modelled the disease in an endemic area, and the effect of the insecticide as a percentage of change in the mortality rate of sandflies, whereas in the present study P per was estimated in a previously CanL-free area and insecticide use was modelled as decreasing the vector density proportionally to its efficacy [8].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have been used to evaluate the individual effect of mitigation measures (MMs) to control CanL infection [6][7][8]. In a simulation model, Dye [9] also evaluated the relative reduction in CanL incidence by varying the (unknown) efficacy of different MMs.…”
Section: Introductionmentioning
confidence: 99%